How to Win Twice at an Auction. On the Incidence of Commissions in Auction Markets - Victor Ginsburgh; Patrick Legros; Nicolas Sahuguet (Fondazione Eni Enrico Mattei (FEEM), 2004)
We analyze the welfare consequences of an increase in the commissions charged by the organizer of an auction. Commissions are similar to taxes imposed on buyers and sellers and the economic problem that results looks similar to the question of tax incidence in consumer economics. We argue, however, that auction markets deserve a separate treatment. Indeed we show that an increase in commissions makes sellers worse off, but some (or all) buyers may gain. The results are therefore strikingly different from the standard result that all consumers lose after a tax or a commission increase. We apply our results to comment on the class action against Christie's and Sotheby's and argue that the method used to distribute compensations was misguided.
Keywords: D44; D80; 330; Auction; Intermediation; Commissions; Welfare; Auktion; Wohlfahrtsanalyse; Auktionstheorie